Teachers' Strategies in Teaching Speaking English at SMA N 15 Padang - Cicilia Ratna Sari; Yetti Zainil (Journal of English Language Teaching, 2020)
AbstractThis study aimed to teachers’ strategy in teaching speaking English. The participants of this research were three teachers grade then in SMA 15 Padang who take the English subject as their elective subject. This study is descriptive research with quantitative. The instrumentation of this research is interview. The research used interview. In collecting the data, classroom observation and interview were conducted to identify the strategies of teaching speaking. The result revealed that the strategies used by the teacher were discussion, simulation, and communication games. The impact of speaking strategies used by the teacher are make students more active in learning, creating learner’s be more positive thinking and increasing the learner’s motivation. Among the three of teacher’s strategies, almost all of the students like the communication game as the strategy in teaching speaking, because they regard communication game can improve their speaking ability, built their motivation to speak, and make the teaching-learning process become more fun. Key words: teaching strategies, teaching speaking